Chronic candidal osteomyelitis of mid face: A therapeutic dilemma - Rishi Bali; Parveen Sharma; Prachi Gupta; Shivani Gaba (Elsevier, 2013)
Numerous explanations have been proposed for the increase in fungal infections including the use of broad-spectrum antibiotics, antineoplastic agents and prosthetic devices. Also increase in proportion of immunocompromised population predisposed to fungal infection might be a contributory factor.Candida albicans is a part of normal flora of the oral cavity. However, it is rarely implicated in maxillary osteomyelitis. Diagnosis of Candida infection is challenging as most symptoms are non-specific and cultures may only become positive late in the course of the infection. Due to scarcity of literature, there are no robust guidelines regarding the most appropriate therapeutic regimens to be employed in such cases.A case of candidal osteomyelitis of mid face is reported suggesting the need for more multicentric long-term studies to formulate and establish appropriate treatment regimens.